Vpliv zadovoljstva z delom na pojav izgorelosti med medicinskimi sestrami - Kavšak, Aleksandra (Obzornik zdravstvene nege, 2021)
Introduction: Workplace satisfaction is a key factor in providing quality nursing care. The purpose of the study was to investigate the view of nurses on work satisfaction and how it contributes to the development of burnout syndrome in nurses.Methods: A descriptive qualitative research method was used. Partially structured interviews were conducted on a dedicated quota sample of 12 nurses employed in primary, secondary and tertiary health care. The acquired data were analyzed using the qualitative content analysis.Results: The following themes were identified: (1) negative work area factors; (2) motivational factors in the workplace; (3) the impact of nurses' satisfaction on their personal lives; and (4) nurses' personal view of work satisfaction. Discussion and conclusion: Nurses believe that it is important to have good interpersonal relationships in the team. Only good interpersonal relationships can secure users of healthcare services professional and quality treatment. Decreasing the incidence of the burnout syndrome in nursing care employees and recognizing it as an issue may be brought about by increasing the awareness of the burnout syndrome. It would be necessary to contribute in designing policy measures to overcome and prevent the problems associated with burnout of nurses at the workplace. Managing stress and burnout should become an integral part of the organizational process as it contributes to an organization's higher productivity. Appropriate guidance and sufficient staffing standards may significantly reduce the costs associated with employee illness since by looking after the health of its employees an organization also contributes to their greater motivation.
Keywords: delovna mesta; healthcare; kakovost življenja; nursing; quality of life; stres; stress; workplaces; zdravstvena nega; zdravstvo